Dynamic response of a quantum wire structure - Yu, Yabin (2018)
We present an investigation of the dynamical response for a quantum wire structure with reservoirs. The capacitance, admittance, and the distribution of internal potential and charge density are calculated. Our numerical calculation for internal potential and charge density shows that the induced charge density is mainly distributed in transition regions between the reservoirs and the wire, and that once any quantum channel opens, the potential drop is very sharp and occurs in the transition regions. Small Friedel oscillations in the charge density as well as charge peaks are observed. We show in our model that in the reservoirs the characteristic potentials tend to unity or zero. The results of capacitance and emittance show the resonant peaks due to the opening of an additional channel, and the oscillations are related to the longitudinal states of the quantum wire. For capacitance, a steplike behavior appears as the number of open channels increase, but for emittance such steplike structure is not observed. Furthermore, we found that the emittance curves may lie either below or above capacitance, so the charge transmission may give positive or negative contributions to the emittance.